Relationship Between Neutrophil Count and 90‐Day Outcomes and Effect of Dual Antiplatelet Therapy in Patients With Acute Ischemic Stroke or Transient Ischemic Attack: A Post Hoc Analysis of the INSPIRES Trial - Yicong Wang; Yuesong Pan; Xuan Wang; Ying Gao; Weiqi Chen; S. Claiborne Johnston; Philip M. Bath; Pierre Amarenco; Cong Gao; Yongjun Wang; Xiaoling Liao; Yilong Wang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Inflammation is an important mechanism in ischemic stroke and high‐risk transient ischemic attack, but clinical inflammatory markers on antiplatelet therapy remain to be studied. This study was designed compare the neutrophil count (NC) on the efficacy and safety of clopidogrel–aspirin with that of aspirin in patients with ischemic stroke or high‐risk transient ischemic attack caused by intracranial or extracranial atherosclerosis. Methods The INSPIRES (Intensive Statin and Antiplatelet Therapy for High‐Risk Intracranial or Extracranial Atherosclerosis) study was a post hoc analysis of the multicenter, randomized, double‐blind, placebo‐controlled, 2‐by‐2 factorial trial. The primary efficacy and safety outcomes were 90‐day stroke and moderate‐to‐severe bleeding. The differences in the efficacy outcome were calculated with cox proportional hazards model and the generalized linear model as well as logistic regression. Results The study included 5929 patients of median age 65 years (interquartile range, 57–71 years), 3800 (64.09%) of whom were men; 1983 (33.45%) had a low NC (≤3.65×109/L), 1973 (33.28%) had an intermediate NC (3.65<NC≤4.97×109/L), and 1973 (33.28%) had a high NC (>4.97×109/L). Patients with ischemic stroke or transient ischemic attack with a higher NC benefited more from clopidogrel–aspirin than from aspirin alone. There was no significant difference in the primary safety outcome of moderate‐to‐severe bleeding according to antiplatelet therapy or NC. Conclusions The post hoc analysis suggested patients with a higher NC obtained greater benefit from clopidogrel–aspirin than from aspirin without an increase in bleeding risk. The findings may serve as a reference indicator for future anti‐inflammatory therapy. However, further research is needed to explore the mechanism.